Features of growth for Mytilus trossulus (Bivalvia: Mytilidae) in various conditions of habitat in the Tauiskaya Bay of the Okhotsk Sea - Vyacheslav S. Zharnikov (Известия ТИНРО, 2016)
Biology of Mytilus trossulus is investigated in the Vesyolaya Cove, the Tauiskaya Bay on June 16 - September 20, 2011 within experimental studies of its cultivation ability in severe conditions of the northern Okhotsk Sea. In case of so called Spanish cultivation technology or its White Sea modification, the mussels grow to the commercial size (35 mm) in 3-4 seasons. To decrease this time to 1-2 seasons, the breeding technology is applied with the mussels collecting from the littoral substrate and their further breeding in hanged collectors. The mussels growth rate is evaluated both on the littoral substrate and in the collectors. The growth rate becomes lower after the mussels transfer from the littoral substrate to the hanged collectors but increases intensively after their transfer from the collectors to the littoral substrate, being higher that for the originally littoral mollusks. The growth rate dependence on size and age of the mussels is considered.